Cardiovascular risk factors in patients with and without a history of atherosclerotic cardiovascular disease in the SANTORINI study and estimation of risk. (3rd October 2022) - Ray, K K; Manu, M C; Burden, A; Catapano, A L
Abstract: Background: Strategies for the prevention of atherosclerotic cardiovascular disease (ASCVD) are related to individual risk factors, and according to guidelines the higher the risk, the more intense the treatment required. Identifying patients at highest risk who might benefit the most from interventions is central for tailored solutions and ASCVD prevention, and any underestimation of risk may increase the ASCVD burden in these patients. Purpose: To describe demographics and cardiovascular (CV) risk factors of patients with and without prior ASCVD enrolled in the SANTORINI study, as well as their CV risk as assigned by the investigator at the time of enrolment. Methods: SANTORINI is an observational study (NCT04271280) conducted in 14 European countries and including patients aged ≥18 years with high- and very-high CV risk, as assessed by the investigator, and requiring lipid-lowering therapy. Patients were recruited between March 2020 and February 2021. The ASCVD status (coronary; cerebral; peripheral/other; polyvascular) of patients was defined based on medical records and the basis for risk classification was documented. For those whose risk was classified by the investigator based on the 2019 ESC/EAS guidelines, the CV risk was re-assessed centrally based on the information present in the study database to assess concordance. Results: A total of 9044 patients were included in the analysis; of these, 76.9% had documented history of ASCVD (Table 1). Overall, the majority of patients were male (72.6%) and had a mean (SD) age of 65.3 (10.9) years. Mean (SD) LDL-C was 2.3 (1.13) mmol/L and 2.8 (1.37) mmol/L in the with and without ASCVD groups, respectively. Hypertension was common in both groups, whereas diabetes and familial hypercholesterolaemia were more prevalent in those without than those with ASCVD (44.6% vs 30.3% and 18.6% vs 7.2%, respectively). Patients with and without ASCVD had multiple CV risk factors (Table 1). Overall, ESC/EAS guidelines were cited as the most commonly used basis for risk classification (52.0%). Among all patients, the investigator assessed 26.0% and 84.2% of patients without and with ASCVD, respectively, as being very high-risk. However, central re-estimation for those using ESC/EAS guidelines suggested that 54.7% and 100% of those without and with ASCVD were at very high CV risk (Table 2). Conclusion: Analysis of the SANTORINI baseline data shows that CV risk factors are common even in patients without documented ASCVD, and that the CV risk of patients both with and without ASCVD is underestimated in clinical practice, potentially contributing to clinical inertia in risk factor control. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Daiichi Sankyo Europe GmbH, Munich, Germany